The judge between law and literature. Reality and fiction of the literary judge and his poetic justice - Hernández Ruiz, Marcos Geraldo (2023)
The judge is the only human being who, without wishing to be God, is obliged to judge his fellow human beings as if he were. However, unlike God, he does not judge humanly by divine grace, but with empathic reason, which becomes his poetic justice. The judge achieves this poetic justice by placing himself between law and literature, metamorphosing himself into a literary judge, a man and a juridical-literary character that God, in his image and likeness, would love with divine justice.